Influence Work Station Design and Firm Constitutional Complaint Against Musculoskeletal on Stone Crusher Worker Progo in Magelang (Public Health Perspective Journal, 2020)
A rock-breaking work that engaged in the informal sector and contain a great job risk to health and safety of workers. Solving Stone in the river Progo an informal jobs into one livelihood. In working stone crushers appears work attitude accordance with his needs. Work attitude or ergonomic working conditions caused by the design of work stations that were not appropriate in turn can lead to complaints such as disorders of the musculoskeletal system. This research is quantitative, using observational design "observational". These samples included 33 respondents. The sampling technique used in this research is purposive sampling.The instrument uses anthropometer set, the meter rolls, verbal nomeric scale questionnaires, observation sheets body constitution, Checklist health conditions, stationery, and cameras., Data collection techniques throughmusculoskeletal complaints data collection before and after work design in the form of appropriate ergonomic chair that has been adapted to the body anthropometric and body constitution by means of direct observation and interviews in the study. Statistical analysis using one-way ANOVA test (one-way ANOVA). The research found p = 0.000, where the value (p 0.05), there is the effect of changes in the work station of the musculoskeletal complaints (skeletal muscle) workers Progo river stone crushers in Magelang, because there is the average difference between the value before work by after work and test results revealed very significant. Z value in the Wilcoxon test was -4.808. Price is negative (-) indicates complaint skeletal muscles before work is smaller than complaints skeletal muscles after work.